Learning through mobile taranum; the analysis and the acceptance - Hassan, Abd Rauf; Kamarudin, Noraziahtulhidayu; Mohd Amiruddin, . (JQSR Editorial Team Universiti Tun Hussein Onn Malaysia, 2024)
Tarannum al-Quran, a melodious recitation style of the Quran, is a revered art form that enriches the spiritual experience of Islamic worship. However, in Malaysia, learning Tarannum is a significant challenge due to the scarcity of qualified teachers. The intricate nature of this art form demands profound knowledge and mastery, which are often limited to a select few. This study aims to address this issue by exploring innovative approaches to teaching and learning Tarannum, making it more accessible to a wider audience and preserving this invaluable Islamic heritage. The method used during this project is Multimedia Mobile Content Development (MMCD) as it is suitable and fast for this project. This project will publish the application in android based and the period for this project is short. The expected result for the project is an application that will ease anyone that is interested in learning Tarannum rather than only watching YouTube videos and others. The acceptance rate for this application is 55 %. This acceptance rate is based on 10 users from Sekolah Kebangsaan Kota Masai who involved in the beta testing.